Production Process Quality Improvement In Ice Cream Manufacturing Using Integrated Pareto Chart and 5M1E Fishbone Diagram - Nurrochmad Ismail, Rizky; Hatta, Mochammad; Susiati, Devi; Johan, Dasman; Arifin, Nofri Yudi; Tjahjani, Ida Kusnawati (Tibuana, 2026)
The research object is the ice cream production process at PT Sejuk Abadi Nusantara, using production and quality-control records from January to June 2024. From 29,530 produced units, 630 defective units were identified, representing a defect rate of 2.13%. Pareto analysis indicated four vital few defects contributing 79.21% of total defects: non-uniform texture, excessive moisture content, uneven color, and non-standard portion size. A 5M1E Fishbone Diagram and 5-Why verification showed that dominant root causes were associated with machine, method, measurement, and human factors, especially freezer-temperature sensor drift, worn freezer gaskets, inconsistent hardening time, weak mixing standard operating procedures, and insufficient operator training. A corrective and preventive action plan was proposed, covering sensor calibration, freezer maintenance, hardening standardization, visual work instructions, operator training, moisture testing, environmental monitoring, and monthly calibration. The proposed actions are projected to reduce total defects from 630 to 222 units per semester, or 64.8%. The study demonstrates how integrated Pareto-Fishbone analysis can transform quality-control records into operational process-improvement decisions for frozen-food manufacturing.